Phasor Measurement Units Allocation Against Load Redistribution Attacks Based on Greedy Algorithm - Ali Rahdan; Ali Khaleghi (Advances in Engineering and Intelligence Systems)
Power grid vulnerability to various cyber-attacks will undoubtedly increase with the widespread use of cutting-edge computer technologies in power systems monitoring and control. A common and effective cyber-attack on power grids is load redistribution (LR), which has the potential to confuse power re-dispatch and result in unneeded load loss. To protect the power system, it is essential to devise strategies for the best distribution of the scarce defensive resources, especially those that take the actions of the attackers into account. In order to stop LR attacks, the best budget allocation and the interplay between attack and defense are examined in this study. In particular, the bi-level modeling of LR attacks incorporates the attack and defense interactions. Based on their importance as targets for cyber protection, a few significant substations are chosen. To reduce the projected load loss subject to the attacker's capability, an efficient budget allocation approach based on greedy algorithm is devised for protecting the key substations. To select the optimum attack method and pinpoint the most vulnerable buses for crucial transmission assets, a quick greedy algorithm is proposed. The proposed approaches are put to the test in various scenarios using an IEEE test system, and the simulation results show that they work. This study provides fresh information on efficiently preventing and reducing the LR attack.